RESEARCH OF THE MARKET OF MINI APARTMENT: Array - Kobzan, S. (Municipal economy of cities. Series: «Economy science», 2020)
The purpose of the article is to investigate the development of a new segment of the real estate market in urban development projects. The definition of a mini apartment - the gostinka. The analysis of the world market of mini-apartments is carried out. There are questions of living of different social groups in society in mini-apartments. A classification of mini-apartments has been developed. Factors significantly affect the cost of a mini-apartment. Conclusions are made about the future market of mini-apartments in the city economy The development of the market of mini-apartments can be considered as a new social phenomenon. Many social groups have access to the purchase of a mini-apartment. The residential real estate market is in a difficult stage now. The economic crisis has had a strong impact on stakeholders. The market of mini-apartments in Ukraine is a new and currently unexplored social phenomenon. The market of mini-apartments is of great importance for urban development and has high uncertainty in further development. Therefore, the development of the market of mini-apartments poses many problems for urban development in the future Today in Ukraine in the real estate market of Kharkiv increased activity in such a segment of real estate as mini-apartments. The results of the research show that the cost range of 1 sq.m. for such objects is very large and ranges from 300 to 1000 US dollars. Which is 2 times lower than the average market prices for typical apartments. Let’s analyze the primary and secondary markets of mini-apartments. The houses in which the mini-apartments are located can be characterized. Mini-apartments in reconstructed houses are of great interest to stakeholders. Here they are much lower than their cost. Mini-apartments are now actively bought by the following social groups and categories of people. Mini-apartments in reconstructed houses are of great interest to stakeholders. Here they are much lower than their cost. The classification of mini-apartments was carried out according to the parameters that significantly affect the prices in the studied segment. They can increase or decrease the market value of such real estate. The price is significantly affected by such a parameter as the ratio of total and living space. The author proposes factors that affect the cost of mini-apartments. Thus, in Ukraine, the market of mini-apartments (hotels) arose and developed due to the unstable economic situation, the devaluation of the hryvnia and declining incomes. Today, renting apartments is expensive, so mini-apartments are the best option for affordable housing. Many people buy mini-apartments as temporary housing. This segment of real estate has a fairly high profitability for investors. The cost of 1 sq m of mini apartments depends on the investment attractiveness of the regional center. Market research and excellent characteristics of mini-apartments. In large cities of Ukraine, especially in Kyiv and Kharkiv, the number of mini-apartments under construction is growing. The analysis of the market showed that such apartments are in demand among stakeholders today. Factors increasing demand for mini-apartments. Conclusions. The researched market of small-sized housing can be considered as a new social phenomenon in large cities of Ukraine. The question of a new segment of the real estate market in urban development projects is highly relevant In Ukraine, the market of mini-apartments (hotels) has emerged and is developing due to the unstable economic situation, the devaluation of the hryvnia and declining incomes. The cost of 1 square meter of mini-apartments depends on the investment attractiveness of the regional center. The whole market of mini-apartments (hotels) in large cities of Ukraine is actively developing. In Kharkov, in most cases, buy small apartments for further rent.